Agroforestry: A way forward for rehabilitation of salty lands for livelihood security and carbon sequestration - Dagar, J.C. (Indian Journal of Agroforestry, 2020)
Nearly one billion hectares of arid and semi-arid areas of the world are salt-affected and remain barren due to salinity or water scarcity. These lands inhibit plant growth owing to the osmotic effects of salt, poor physical conditions leading to poor aeration, nutrition imbalances and toxicities. With the increasing demand for good quality land and water for urbanization and developmental projects, in future agriculture will be pushed more and more to the marginal lands particularly in developing countries. With use of appropriate planting techniques and salt-tolerant species, the salt-affected lands can be brought under viable vegetation cover. Further, in most of the arid and semi-arid regions the ground water aquifers are saline. Concerted research efforts have shown that by applying appropriate planting and other management techniques (e.g. sub-surface planting and furrow irrigation), the degraded salty lands (including calcareous) can be put to alternative uses (agroforestry), and salt-tolerant forest and fruit trees, forage grasses, medicinal and aromatic and other high value crops can be equally remunerative. Such uses have additional environmental benefits including carbon sequestration and biological reclamation. Agroforestry is not only a necessity for increasing tree cover and hence decreasing pressure on natural forests, but also a most desired land use especially for reclaiming and rehabilitating the degraded and salty lands. These opportunities for raising salt-tolerant crops and alternate land uses through agroforestry on salty and waterlogged areas have been discussed in this paper.